2011
DOI: 10.1159/000327242
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Specific Differences in Perinatal Rodent Oligodendrocyte Lineage Progression and Its Correlation with Human

Abstract: occurred latter than in white matter. The hippocampus also displayed a later onset of preOL maturation in all three strains, such that OL lineage maturation and early myelination was not observed to occur until about P14. This timing of preOL maturation in rat cortical gray matter coincided with a similar timing in human cerebral cortex, where preOL also predominated until at least 8 months after full-term birth. These studies support that strain-specific differences in OL lineage immaturity were present in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 40 publications
6
65
1
Order By: Relevance
“…Rodents are altricial, with relatively immature brains at birth. Newborn rodents from P1 to P3 predominantly express preoligodendrocytes in the white matter, without evidence of myelination [78,79], consistent with the human fetus at 23-32 weeks. By P7 extensive oligodendrocyte maturation occurs in rodents, coinciding with the onset of early myelination, which is broadly consistent with late preterm to near term in human infants.…”
Section: Postnatal Infection/inflammation In Rodentsmentioning
confidence: 96%
“…Rodents are altricial, with relatively immature brains at birth. Newborn rodents from P1 to P3 predominantly express preoligodendrocytes in the white matter, without evidence of myelination [78,79], consistent with the human fetus at 23-32 weeks. By P7 extensive oligodendrocyte maturation occurs in rodents, coinciding with the onset of early myelination, which is broadly consistent with late preterm to near term in human infants.…”
Section: Postnatal Infection/inflammation In Rodentsmentioning
confidence: 96%
“…Thus, the investigator can choose the appropriate developmental timing for the insult to be evaluated. Although in both humans and sheep, myelination begins prenatally, a notable difference is that myelinogensis progresses more rapidly in sheep [41] than in humans [43], which continues to progress for months after term birth [44]. By contrast, the rodent displays accelerated white matter maturation and myelination that occurs entirely postnatally [45].…”
Section: Advantages and Disadvantages Of The Fetal Sheep To Model Wmimentioning
confidence: 99%
“…By contrast, the rodent displays accelerated white matter maturation and myelination that occurs entirely postnatally [45]. In neonatal rats, for example, the progression from human preterm equivalent to near-term equivalent oligodendrocyte maturation occurs rapidly during the first 5 days after birth [44].…”
Section: Advantages and Disadvantages Of The Fetal Sheep To Model Wmimentioning
confidence: 99%
“…As previously described, the majority of OLs at P6 in the periventricular white matter and cortex are O4 and O1 positive and not myelin basic protein (MBP) expressing (21,25). To test the hypothesis that NKCC1 was present on developing premyelinating OLs in white matter, immunostaining was done in the naive immature rat by double labeling for NKCC1 and the cell marker GalC (Figure 2a-c).…”
Section: Nkcc1 Is Expressed On Developing Ols and Neurons In The Immamentioning
confidence: 98%
“…The end of the first postnatal week (P5-7) in rodents is a period of heightened white matter vulnerability to HI compared to earlier or later ages (21,22). We have previously shown that this developmental stage is associated with higher levels of NKCC1 in cortical homogenates compared to adult (10).…”
Section: Nkcc1 Expression In the White Matter Peaks Early In The Perimentioning
confidence: 99%